Nutritional Evaluation Of Cassabio In The Ration Of Local Lambs - Diapari, D.; Lubis, A.D.; Thaher, R.R; Ifafah, W.W.; Astuti , D.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The objective of the study was to evaluate the effect of Cassabio inclusion in concentrate on performance of local lambs. Twelve thin tailed lambs, aged 6 - 8 months with an average BW 13-16 kg, were divided into four treatment groups with three replicates by using completely Randomized Block Design ie. without Cassabio (C-0), 20% Cassabio (C-20), 40% of Cassabio (C 40), and 60% of cassabio (C-60). Variables measured were feed consumption, average of body weight gain, and feed efficiency. No significant difference in body weight gain, feed comsumption and feed efficiency was observed on addition of Cassabio upto 60 % in the concentrate..